Control interno y gestión del talento humano en la unidad de gestión educativa local, Requena año 2023 - Bernuy Zagaceta, Jhoana Marilia (2024)
The main objective of this report was to determine the relationship between internal control and human talent management at the Local Educational Management Unit (UGEL) of Requena in the year 2023. This research adopted a quantitative approach, involving the collection and analysis of numerical data to reach specific and well-defined conclusions. One of the most significant findings of this study was in Table No. 3, where a Pearson correlation of 0.797 was obtained, suggesting a strong positive relationship between the examined variables. Additionally, the bilateral sigma value was 0.000, indicating high statistical significance. To confirm the relationship between both variables, the p-value was calculated. The p-value turned out to be less than 0.05, leading to the acceptance of the hypothesis (H1) proposed in the study. Consequently, we can affirm that the hypothesis stating "Internal control is significantly related to human talent management at the Local Educational Management Unit, Requena 2023" has been validated. These findings support the importance of maintaining effective internal oversight at UGEL Requena, as it is closely related to the successful management of human talent in this institution during the year 2023.